Ashkenazi Jewish population screening for Tay–Sachs disease: The International and Australian experience. (13th June 2014) - Lew, Raelia M; Burnett, Leslie; Proos, Anné L; Barlow‐Stewart, Kristine; Delatycki, Martin B; Bankier, Agnes; Aizenberg, Harry; Field, Michael J; Berman, Yemima; Fleischer, Ronald; Fietz, Michael
Abstract Internationally, Tay‐Sachs disease (TSD) preconception screening of Ashkenazi Jewish (AJ) individuals and couples has led to effective primary prevention of TSD. In Australia, adolescent preconception genetic screening programs operate mainly in Jewish community high schools. These existing programs offer an effective means of primary prevention of TSD, are cost effective and safe. However, in the broader Australian community TSD screening is not systematically performed and cases still occur in unscreened AJ individuals. In order to improve the effectiveness of Australian screening, there is a need for definitive guidelines for healthcare professionals to facilitate extension of the proven benefits of preconception TSD screening to all AJ individuals at risk. We performed a systematic review of the relevant literature relating to AJ pre‐conception and antenatal screening for TSD. The evidence was assessed using an established National Health and Medical Research Council evidence grading system. Evaluations of efficacy of TSD screening programs design and execution, cost‐benefit and cost‐utility health economic evaluation, and population outcomes were undertaken. The results have been used to propose a model for universal AJ TSD preconception and antenatal screening for the primary care setting.